2001
DOI: 10.1097/00008469-200112000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Malmö diet and cancer study: representativity, cancer incidence and mortality in participants and non-participants

Abstract: In order to investigate potential selection bias in population-based cohort studies, participants (n = 28098) and non-participants (n = 40807) in the Malmö Diet and Cancer Study (MDCS) were compared with regard to cancer incidence and mortality. MDCS participants were also compared with participants in a mailed health survey with regard to subjective health, socio-demographic characteristics and lifestyle. Cancer incidence prior to recruitment was lower in non-participants, Cox proportional hazards analysis yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
493
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 454 publications
(510 citation statements)
references
References 19 publications
17
493
0
Order By: Relevance
“…Some additional methodological concerns should be addressed. The participation rate in the MDCS was 40%, and a previous study on the background population has shown a selection of higher socioeconomic status in participants (35). The participating women in the MDCS were often postmenopausal; hence, the risk factors elucidated from this study may primarily cover postmenopausal breast cancer.…”
Section: Discussionmentioning
confidence: 80%
“…Some additional methodological concerns should be addressed. The participation rate in the MDCS was 40%, and a previous study on the background population has shown a selection of higher socioeconomic status in participants (35). The participating women in the MDCS were often postmenopausal; hence, the risk factors elucidated from this study may primarily cover postmenopausal breast cancer.…”
Section: Discussionmentioning
confidence: 80%
“…These people tend to be healthier than others (Manjer et al 2001). A comparison with a public health survey covering 74.6% of the same age cohort suggests that the MDCS population (see Methods), of which our population comprised a random sub-sample, was selected toward better health than the general population (Manjer et al 2001).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…A comparison with a public health survey covering 74.6% of the same age cohort suggests that the MDCS population (see Methods), of which our population comprised a random sub-sample, was selected toward better health than the general population (Manjer et al 2001). Both these circumstances may have biased the estimated effects toward the null, but there may also be other effects of selection bias due to the participation rate of only 41%.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 40.8% of the eligible population completed the whole study which consisted of a baseline questionnaire (at T0) and anthropometric testing and blood samples. Comparison with a public health survey (Lindström, Bexell, Hanson, & Isacsson, 1995;Lindström, Sundquist, & Östergren, 2001), covering 74.6% of the same age cohort, suggests that the MDCS population sample was selected towards better health than in the general population (Manjer, Carlsson, Elmstahl, Gullberg, Janzon, Lindström et al, 2001).…”
Section: Design and Populationmentioning
confidence: 99%